The value-added of sectoral disaggregation: Implications on competitive consequences of climate change policies - Victoria Alexeeva-Talebi; Christoph Böhringer; Andreas Löschel; Sebastian Voigt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Global impact assessment of unilateral climate policies is commonly based on multi-sector, multi-region computable general equilibrium (CGE) models that are calibrated to consistent accounts of production, consumption, and bilateral trade flows. However, global economic databases such as GTAP treat energy-intensive and trade-exposed industries rather in aggregate, thereby missing potentially important details on the heterogeneity of these sectors. In this paper, we elaborate on the availability of data resources and methodological issues in disaggregating energy-intensive and tradeexposed sectors that receive larger attention in the public policy debate on unilateral emission regulation: non-ferrous metals, iron and steel and non-metallic minerals. Our sensitivity analysis revolves around three types of unobserved heterogeneity at the sub-sectoral level: trade elasticities, energy consumption and technology specifications. Drawing on the example of border tax adjustments, we find that for all given technology specifications and variation in energy shares, the biggest differences emerge from variations in Armington elasticities. Even moderate changes in Armington elasticities can alter the magnitude and the sign of the effects at the sectoral level. The implications of sub-sectoral disaggregation are not as pronounced for macroeconomic indicators and leakage as for sectoral indicators.
urn:nbn:de:bsz:180-madoc-326210
Keywords: D58; H21; H22; Q48; 330; sectoral disaggregation; emissions trading; border adjustment; competitiveness; carbon leakage; Klimaschutz; Emissionshandel; Branche; Aggregation; Energiekonsum; Border Tax Adjustment; Internationaler Wettbewerb; Elastizität; Allgemeines Gleichgewicht; Theorie